A plea for trade theory in economic history - Findlay, Ronald (Economic & Social Studies, 1998)
This paper discusses the applicability of the small-scale general equilibrium models of trade theory to the problems of economic history. The examples are drawn from the experience of the Atlantic economy from its emergence to the end of the nineteenth century.
Dublin Economic Workshop guest lecture, Twelfth Annual Conference of The Irish Economic Association, Radisson Roe Park Hotel, Limavady, 24-26 April, 1998
Keywords: Trade; Economic history; Economic theory